Delineation and Assessment of Hab watershed, Balochistan, Pakistan through Geo-spatial Technology: Delineation and Assessment of Hab watershed, Balochistan, Pakistan through Geo-spatial Technology - Rakhshanda Sadaf; Syed Jamil H. Kazmi; Isma Younes; Sadia Khaleeq (International Journal of Economic and Environmental Geology, 2017)
Water is one of the key elements of life and Pakistan is facing acute water shortage. The problem is more severe in the mega cities like Karachi and nearby areas in which industries and population are growing at a very high rate. Presently, Karachi is getting only about 55 percent of water against its fast increasing requirements leading to water crises in Karachi city. The Hab River is one of the main and important water supply sources for Hab industrial estate and Karachi. Therefore, it is extremely important to study this area with an aim to explore, develop and exploit its water resources for the current and upcoming requirements of the area. This paper is about the investigation of the potential of water resources in the Hab watershed through geo-informatics. Hydrological modeling has been done in GIS environment, which outlines a complete picture of Hab watershed and provides assessment of the potential of the watershed located in the Balochistan province of Pakistan. Watershed boundaries have been established and its area has been estimated in GIS environment. Considering the large area, Hab watershed has been categorized as macro watershed. Drainage characteristics of the watershed have been defined through GIS datasets, which were derived by performing drainage analysis on a terrain model. Other key contributions of the study include stream network analysis, flow accumulation and flow pattern analysis of the watershed. Keywords: Geo-informatics, hydrological modeling, delineation, drainage network, watershed.